" . . . I Should Maintain a Healthy Life Now and Not Just Live as I Please . . . ": Men's Health and Fatherhood in Rural South Africa. (November 2016) - Hosegood, Victoria; Richter, Linda; Clarke, Lynda
This study examines the social context of men's health and health behaviors in rural KwaZulu-Natal, South Africa, particularly in relationship to fathering and fatherhood. Individual interviews and focus groups were conducted with 51 Zulu-speaking men. Three themes related to men's health emerged from the analysis of transcripts: (a) the interweaving of health status and health behaviors in descriptions of "good" and "bad" fathers, (b) the dominance of positive accounts of health and health status in men's own accounts, and (c) fathers' narratives of transformations and positive reinforcement in health behaviors. The study reveals the pervasiveness of an ideal of healthy fathers, one in which the health of men has practical and symbolic importance not only for men themselves but also for others in the family and community. The study also suggests that men hold in esteem fathers who manage to be involved with their biological children who are not coresident or who are playing a fathering role for nonbiological children (social fathers). In South Africa, men's health interventions have predominantly focused on issues related to HIV and sexual health. The new insights obtained from the perspective of men indicate that there is likely to be a positive response to health interventions that incorporate acknowledgment of, and support for, men's aspirations and lived experiences of social and biological fatherhood. Furthermore, the findings indicate the value of data on men's involvement in families for men's health research in sub-Saharan Africa.